Molybdenum blue nano-rings: an effective catalyst for the partial oxidation of cyclohexane. Issue 1 (30th October 2014) - Liu, Xi; Conte, Marco; Weng, Weihao; He, Qian; Jenkins, Robert L.; Watanabe, Masashi; Morgan, David J.; Knight, David W.; Murphy, Damien M.; Whiston, Keith; Kiely, Christopher J.; Hutchings, Graham J.
Abstract : Molybdenum blue (MB), a multivalent molybdenum oxide with a nano-ring morphology is well-known in analytical chemistry but, to date it has been largely ignored in other applications. Abstract : Molybdenum blue (MB), a multivalent molybdenum oxide with a nano-ring morphology is well-known in analytical chemistry but, to date it has been largely ignored in other applications. In the present work, MB has been characterized by STEM-HAADF imaging for the first time, showing the nano-ring morphology of this complex molybdenum oxide and the ordered super-molecular framework crystals that can result from the self-assembly of these MB nano-ring units. The potential of MB as an oxidation catalyst has also been investigated, where it is shown to have excellent catalytic activity and stability in the selective oxidation of cyclohexane to cyclohexanol and cyclohexanone which are important intermediates in the production of nylon.